Insult to renew, destroy to build: rectifying the disasters of war by Francisco Goya (Palíndromo, 2023)
In 2003, the Chapman brothers purchased 80 originals by Goya with the aim of using them in their work. This act polemicized the commitment expected of the owner, as well the artistic limits, since authentic images were rectified. From the contextualization of the set of engravings known as the Disasters of War to the interpretation of the work Insult to Injury, in this paper we propose to analyze the meaning of the attack that victimized one of the greatest examples of art. It found that there was sense in the act named as cultural vandalism, capable of enhancing and re-signifying the rectified works.
Keywords: Francisco Goya; disaster of war; Jake & Dinos Chapman; cultural vandalism